Report to the Chairman, Subcommittee on Human Resources and Intergovernmental Relations, House Committee on Government Reform and Oversight - Horvitz, Eric (Consumer Health Informatics - Emerging Issues, 1996)
While administrative and diagnostic hospital-based information systems have used computer technology for over 30 years, public- and private-sector organizations have only in the past 10 years or so developed the capability to disseminate health information to millions of people nationwide. Over the past decade, in fact, several hundred new consumer health information systems—called informatics—have been developed. Today’s consumers are demanding more—and more detailed—health information, and are taking a more active role in making medical and lifestyle decisions. Studies on the value of consumer health informatics have highlighted the systems’ ability to respond to consumers’ information needs quickly and efficiently, and reduce the need for some unnecessary medical services, thereby lowering health care costs. The systems are capable of providing many different types of information—often customized—with which consumers can, for instance, review the pros and cons of elective surgery or provide physicians with preoperative health information, potentially avoiding unnecessary preoperative tests.